UJI AKTIVITAS ANTIBAKTERI FRAKSI ETANOL DAUN PEGAGAN (Centella asiatica (L.) Urb) TERHADAP BAKTERI PENYEBAB JERAWAT (Propionibacterium acne) - Febriyanto, Geri; duwi, sandra (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2025)
Acne is a common skin disease throughout the world, especially among teenagers, but acne can also attack adults as well as men and women. The prevalence of acne in Southeast Asia ranges from 40-80% of cases. The prevalence of acne sufferers in Indonesia ranges from 80-85% to adolescents aged 15-18 years. Gotu kola leaves (Centella asiatica (L.) Urb) are a medicinal plant that contains antibacterial substances such as alkaloids, flavonoids, tannins and saponins which provide antibacterial effects. This study aims to determine the activity of the 96% ethanol fraction of gotu kola leaves (Centella asiatica (L.) Urb) against the acne-causing bacteria Propionibacterium acnes as an antibacterial which was tested using the disc diffusion method. Gotu kola (Centella asiatica (L.) Urb) leaves were fractionated by maceration using 96% ethanol then followed by fractionation using ethylacetate and n-hexane then continued with a rotary evaporator, then tested for antibacterial activity with concentration variants of 20%, 40%, 60 % and 80%, the positive control used clindamycin, and the negative control used distilled water. The method used is the disc diffusion method to determine the bacterial inhibition zone. The results obtained showed that the 96% ethanol fraction of gotu kola leaves (Centella asiatica (L.) Urb) was able to inhibit Propionibacterium acnes bacteria with a concentration of 80% with an average diameter of 19.33 mm in the strong category. Data analysis used the One Way Anova which obtained a sig value. 0.000 (0.005). This shows that there is a significant difference with variations in the concentration of the 96% ethanol fraction of gotu kola leaves (Centella asiatica (L.) Urb). The conclusion of this research is that the ethanol fraction of gotu kola leaves (Centella asiatica (L.) Urb) is able to inhibit the acne-causing bacteria Propionibacterium acnes.